DAMPAK PENERAPAN ACFTA TERHADAP GLOBALISASI INDUSTRI JAMU DAN HERBAL INDONESIA - Aisyah Pia Asrunputri (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2017)
This research explains the impacts of ACFTA on the industrial globalization in theIndonesian jamu and herbal industry. Industrial globalization itself is crucial for thedevelopment of a country. The development of a country is needed for the welfare of thepeople and the industrial globalization helps to smooth the process out by allowing thecountry to connect and integrate with the global world through international trade andinvestment aided by information technology in order to achieve the objective, which is thedevelopment itself. Indonesia is one of the countries, which has the privilege in havingintegration with the global world through international agreements. One of theinternational agreements that Indonesia has signed is called ASEAN-China Free TradeArea (ACFTA). ACFTA is a multilateral agreement comprised of the agreements betweenASEAN member countries with China in order to minimalize the trade barriers not onlyfrom the tariff wise but also non-tariff wise between the member countries. Indonesia asone of the member countries has experienced some positive impacts from this internationalagreement such as the increase of the level of its economic development and globalnetworking. However, there are some negative impacts in implementing this internationalagreement from the perspective of the sale of Chinese illegal herbal commodities inIndonesia that contains hazardous materials and the spread of Chinese illegalmanufactures of herbal products in Indonesia. The government of Indonesia is expected tomitigate these issues by formulating and implementing strict trade policy and alsomaintaining the quality of the imported and exported products in order to succeed thisinternational agreement.